2023
DOI: 10.1037/men0000455
|View full text |Cite
|
Sign up to set email alerts
|

The sum of it all: Meta-analyses and metasyntheses in the psychology of men and masculinities.

Jeffrey C. Valentine,
Y. Joel Wong

Abstract: Meta-analyses and metasyntheses perform a crucial role in advancing a field of study by highlighting themes and patterns that emerge from a large body of research, yet they remain utilized research methods in the psychology of men and masculinities. Therefore, in this special issue on research syntheses in the psychology of men and masculinities, we showcase three metasynthetic studies and four meta-analytic studies that address men’s victimization experiences with sexual violence, experience of breast cancer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Indeed, in meta-analytic studies examining masculine norms tied to muscularity, the largest effect sizes were observed between muscularity and adherence to norms related to dominance, achievement, and the pursuit of status (Murnen et al, 2023). This implies that conforming to masculine ideals associated with power is closely linked to concerns about muscularity (Valentine & Wong, 2023). Repeated, and rapid, exposure to this imagery while scrolling across social media content reinforces a cycle of male self-objectification and body dissatisfaction (Seekis et al, 2021), which ultimately can reinforce negative masculine norms of powerlessness or inadequacy, contribute to poor mental health outcomes among men, and reduce their likelihood to seek help for maladaptive thinking (Parent et al, 2019; Shepherd & Rickard, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in meta-analytic studies examining masculine norms tied to muscularity, the largest effect sizes were observed between muscularity and adherence to norms related to dominance, achievement, and the pursuit of status (Murnen et al, 2023). This implies that conforming to masculine ideals associated with power is closely linked to concerns about muscularity (Valentine & Wong, 2023). Repeated, and rapid, exposure to this imagery while scrolling across social media content reinforces a cycle of male self-objectification and body dissatisfaction (Seekis et al, 2021), which ultimately can reinforce negative masculine norms of powerlessness or inadequacy, contribute to poor mental health outcomes among men, and reduce their likelihood to seek help for maladaptive thinking (Parent et al, 2019; Shepherd & Rickard, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Definitions of masculinities in PSMM (Addis et al, 2010; Valentine & Wong, 2023) often leave white American masculinities uninterrogated (Liu, 2017; Wong & Wang, 2022). Researchers understand the descriptor, “dominant,” especially in the United States, as a proxy term for “white” or “whiteness,” referring to the broader categories of European, cisgender, heterosexual, and middle-class masculinities (Levant & Powell, 2017; Wedgwood et al, 2023).…”
Section: Intersectionality and White Masculinities?mentioning
confidence: 99%
“…Although the psychological study of men and masculinities (PSMM) field has continued to develop (Addis et al, 2010; Valentine & Wong, 2023), notions of white masculinities have remained mostly uninterrogated (Liu, 2017; Wong & Wang, 2022). In this article, we emphasize the unexamined “whiteness” and assumed Americanness of masculinities research and scholarship (Liu, 2017) and use a racial–spatial framework to explore how systemic racism renders differential racialized experiences for white men when compared with the racialized experiences of men of Color (Liu et al, 2023).…”
mentioning
confidence: 99%